Some speculation about the risks of negotiate the political peace process based on violent cultural game rules. The case of Colombian catholic religious values (2015)
The article speculates about the Colombian catholic cultural values incidence  over the actual peace process. Our hypothesis suggests that the violent political profile of Catholic values acting as the game rules of the peace process conspires against the negotiations accuracy as well as against the agreements implementation sustainability. The article describes some signals about Colombian catholic culture genealogy and its relationships whit the historically persistent violence status of this country. Based upon these assumptions, it applies some Game Theory tools to evaluate the actual peace process negotiation between Colombian government and FARC insurgency in which the rules are influenced by the Catholic warrior values. And it concludes that while peace negotiators do not substitute the actual zero sum game linked to a Prisoners Dilemma´s game with Lost-Lost solution, instead of playing a Win-Win solution game linked to Insurance mechanism, the peace process and the post implementation of its agreements will continue to be highly risky as well as unsustainable.